Beneficial Effects of Warming Temperatures on Embryonic and Hatchling Development in a Low-Latitude Margin Population of the High-Latitude Lizard Lacerta agilis - Cui, Luoxin; Yang, Cheng; Zhang, Decheng; Lin, Shu; Zhao, Wenge; Liu, Peng (Frontiers in Ecology and Evolution, 2022)
The effects of warming temperatures on embryonic and hatchling development are critical for determining the vulnerability of species to climate warming. However, these effects have rarely been investigated in high-latitude oviparous species, particularly in their low-latitude margin populations. This study investigated the embryonic and hatchling development and fitness-related traits of a low-latitude margin population of a high-latitude lizard (Lacerta agilis). These traits were examined under present (24 ℃), moderate warming (27 and 30 ℃), and severe warming scenarios (33 ℃). Based on embryonic and hatchling responses to thermal variation, this study aimed to predict the vulnerability of the early life stages of low-latitude margin population of Lacerta agilis to climate warming. The incubation period of the low-latitude margin population of Lacerta agilis decreased as the temperature increased from 24 to 33 °C. Hatching success was similar at 24 °C, 27 °C, and 30 °C but decreased significantly at 33 °C. No differences with temperature were observed for hatchling snout-vent length and hatchling body mass. The sprint speed was higher for hatchlings from temperatures of 24 °C and 33 °C. The growth rate of hatchlings was highest at 30 °C; however, the survival rate of hatchlings was not affected by the thermal environment. This study demonstrated that even for a low-latitude margin population of the high-latitude lizard, Lacerta agilis, moderate warming (i.e., 27 and 30 °C) would benefit embryonic and hatchling development. This was indicated by the results showing higher hatching success, growth rate, and survival rate. However, if temperatures increase above 33 °C, development and survival would be depressed significantly. Thus, low-latitude margin population of high-latitude species Lacerta agilis would benefit from climate warming in the near future but would be under stress if the nest temperature exceeded 30 °C.